PEMANFAATAN BLOG DAN SEO (SEARCH ENGINE OPTIMIZATION) DI ERA DIGITAL BAGI MAHASISWA JURNALISTIK - Simatupang, Yunita; Zanynu, M. Aswan; Dasmin, Dasmin; Wekogandhigrahita, Alfiansyah; Meldianto, Meldianto; Nurfadila, Nurfadila; Tunda, Amin (Universitas Halu Oleo, 2024)
A blog is a type of website or online platform that contains a series of posts or articles periodically, usually written in an informal style or conversational writing style. SEO (Search Engine Optimization) is an effort or strategy to be applied to a website, blog or page that is ranked at the top of search engines such as Google. Blogging is important for SEO because every new blog that is posted will display a new URL. This new URL opens up new opportunities to be at the top of the search engine. Blogs and SEO also have many benefits for students, including students can hone their writing skills, both in academic and non-academic contexts and understanding SEO allows students to create content that is easy to find in search engines. This increases the visibility of their blogs, making them more effective in reaching a wider audience.